2014
DOI: 10.1186/1478-4491-12-36
|View full text |Cite
|
Sign up to set email alerts
|

Aging village doctors in five counties in rural China: situation and implications

Abstract: BackgroundThe aging population, rapid urbanization, and epidemiology transition in China call for the improvement and adaptation of the health workforce, especially in underserved rural areas. The aging of village doctors (the former “barefoot doctors”) who have served the rural residents for many decades has become a warning signal for the human resources for health in China. This study aims to investigate the village doctors’ aging situation and its implications in rural China.MethodsThe data reviewed were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 43 publications
0
29
0
2
Order By: Relevance
“…Older PHCWs with more years of clinical practice were less likely to access the computer and might not have been familiar with computer and internet use. Recent studies in rural China reported more than 30% of the village doctors in the sample areas (both developed and under-developed regions) were aged 50 or above [ 48 , 49 ]. As computer literacy is essential to implementing web-based training [ 21 ], efforts are needed to help older individuals develop computer skills.…”
Section: Discussionmentioning
confidence: 99%
“…Older PHCWs with more years of clinical practice were less likely to access the computer and might not have been familiar with computer and internet use. Recent studies in rural China reported more than 30% of the village doctors in the sample areas (both developed and under-developed regions) were aged 50 or above [ 48 , 49 ]. As computer literacy is essential to implementing web-based training [ 21 ], efforts are needed to help older individuals develop computer skills.…”
Section: Discussionmentioning
confidence: 99%
“…The shortage and maldistribution of these professionals is a serious problem worldwide, 2 , 3 , 4 , 5 , 6 , 7 whereas the brain drain 8 and ageing of the workforce are additional problems exacerbating the situation. 9 , 10 In SA, the shortage and unequal distribution of medical doctors, with too few doctors servicing rural communities, is not a new phenomenon 11 , 12 and has been highlighted in the national media. 13 , 14 , 15 , 16 , 17…”
Section: Introductionmentioning
confidence: 99%
“…In most countries around the world, there is no mandatory retirement age for doctors. Countries such as the UK and Germany recently phased out their policies on a mandatory retirement age.…”
Section: Discussionmentioning
confidence: 99%